LOCAL WISDOM FISHERMEN SOCIETY IN KEEPING COASTAL ENVIRONMENT IN SURANTIH VILLAGE DISTRICT OF SUTERA - Diandri, Novi - (Pendidikan Geografi, 2014)
The influence of local culture systems has given rise to ways of thinking and acting thatlooked at the relationship of man and the physical universe is an internal relationship that ispersuasive, so the sustainability of aquatic biological resources can be maintained. The objectivewas to obtain data or information and in-depth local knowledge of fishing communities inprotecting the environment in the coastal areas Surantih village District of Sutera. in terms of: 1)Public awareness of the importance of sustainability for the coastal areas of life, 2) Publicconfidence in the sustainability of the coastal environment to ensure survival, 3) Communityunderstanding of the wisdom in keeping coastal areas is necessary, because the coastal area is onesource of life and 4) community Habits coastal environment including either because the toolsused to catch fish.The research is a qualitative systems approach seeks local culture systems In PeoplesFishermen Keeping Coastal Environment in Surantih village District of Sutera, the informant wastaken by purposive sampling technique consisting of fishermen and village trustee conducted thedata analysis techniques with data reduction, data presentation and conclusion.The results showed: 1) Public awareness of the importance of the preservation of thecoastal areas of life seen from a willingness to be responsible about the sustainability of coastalareas in the form of a ban on the use of bombs that can destroy fish habitat as well as the sanctionsfor violators of these regulations, 2) Confidence communities with environmental sustainabilitycoast can ensure the survival, the presence of local wisdom that prohibit fishing using bombs is atestament to the community support that makes the rules against violators of rules that have beenmade jointly by the community, 3) community understanding of the wisdom in keeping coastalareas is needed, coastal region is one source of life and 4) community Habits coastal environmentincluding either because the tools used to catch fish.